Prevalence of Vancomycin Resistant Enterococci Species in Minced Buffalo Meat of Chitwan, Nepal - Ghimire, Sudeep; Basnet, Hom Bahadur; Joshi, Lok Raj; Sapkota, Maheshwar (International Journal of Applied Sciences and Biotechnology, 2014)
Vancomycin resistant Enterococci is becoming one of the concerns of public health in recent times. VRE involve those strains of Enterococci that are resistant to the vancomycin which is considered as last drug of choice for the Gram positive bacterial infections. Studies show enterococci to be one of the major food borne diseases and medical consequences of its occurrence in humans. Thus, a cross sectional studywas carried out to determine the prevalence of VRE in buffalo meat in Chitwan. A total of 63 retail minced meat samples were collected from different meat shops. These samples were diluted and cultured and subjected to antimicrobial susceptibility test. Of 63 samples, 16 (25.39%) samples were positive for the enterococcus species among which 3 (18.15%), were VRE indicating overall prevalence of VRE to be 4.76%.AST reveled that resistance among them was high for penicillin G and amikacin (75%) followed by tetracycline (43.75%), erythromycin (37.5%), vancomycin (18.75%) levofloxacin ( 12%) and methicillin. Even though methicillin revealed no resistance it showed intermediate sensitive to all the samples. Thus, it clarifies the presence of VRE in meat samples suggesting zoonotic disasters that can follow. DOI: http://dx.doi.org/10.3126/ijasbt.v2i4.11123 Int J Appl Sci Biotechnol, Vol. 2(4): 409-412